DISSOLUTION TEST OF SESEWANUWA LEAF FRACTION TABLETS WITH VARIOUS BINDERS USING UV-VIS SPECTROPHOTOMETRY - Arlan Imran; Adinda Dj Tawape; Zulfiayu Sapiun; Prisca S Wicita (LLDIKTI X Sumbar, Riau, Jambi, Kepri, 2026)
The sesewanua plant has potent anti-inflammatory activity, particularly in the n-Hexane: Ethyl Acetate fraction, which contains alkaloid compounds. However, consuming the fraction can cause discomfort, making it important to develop it into a tablet for more practical use. Binders are used in tablet formulations because they bind the tablet components and affect tablet quality. This study aimed to determine the effect of the type of binder (PVP, starch, and Na-CMC) on the dissolution test results of N-Hexane: Ethyl Acetate Fraction tablets using UV-Vis spectrophotometry. The dissolution test was conducted to evaluate how quickly the active ingredient dissolves from the tablet. Four formulas were tested: F0 (without binder), F1 (5% PVP), F2 (5% starch), and F3 (5% Na-CMC). The formula with the best results was F2, containing 5% starch as the binder, with a dissolution percentage of 80.91%. This is because starch is the best binding agent because it can increase the percentage of active ingredient dissolution in tablets. Therefore, it can be said that the addition of starch provides the best results with a dissolution percentage that meets the requirements.